Is digital transformation the key to eradicate financial exclusion in Mexico? - Rojas Ortiz, Oscar Pablo; Lara Gómez, Graciela (Cooperativismo & Desarrollo, 2025)
In a context of disruptive innovation and digital transformation in Mexican financial sector the phenomenon of financial products and services digitalization is being studied. Where disruption has changed the way people interact in the economic and financial system, where financial services digitalization is considered the key factor in reducing financial exclusion. The research was conceptualized using a quantitative approach, exploratory and descriptive in nature, with a cross-sectional design, aimed at generating empirical evidence through the observation of the phenomenon via a panel data model spanning 13 years. The findings indicate that a significant number of financial entities lack both digital and analog strategies. At the municipal level, the data reveal a high concentration of both analog and digital operations in municipalities with populations exceeding 100,000 residents. The dimensions of financial inclusion must be redefined to democratize access to financial services. Rural areas reveal a clear gap in digital product and services adoption, where credit unions prevail, and analog operations remain dominant; Digitalization faces numerous risks; however, technological innovation simultaneously facilitates access to financial services. Nevertheless, access constitutes only one dimension of financial inclusion.